THE USE OF FIRST LANGUAGE IN ENGLISH AS FOREIGN LANGUAGE CLASSROOM - Iitha Priyastiti (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
Discussions of the second language (L2) pedagogy have been studied not only in the language and education fields. Experts working in the psychology field also propose theories on applied linguistics because L2 acquisitions involve external and internal processes. However, despite numerous studies on the field, it appears that an issue regarding the use of first language (L1) still creates continuous debates. Although arguments opposing the use of first L1 present compelling theories as to their rationale, they appear to overlook the context in which teaching and learning process takes place. The studies were either conducted in English as a Second Language (ESL) or English as a Foreign Language (EFL), where teachers are native speakers who do not share the same L1 with students. Considering the uniqueness in classroom contexts, this paper is not going to argue or take sides on the conflicting views on the use of L1. Instead, it attempts to acknowledge the gap of the context in language teaching used in previous studies. Using a sociocultural theory, this article will describe the beneficial use of L1 with a focus on its use by teachers in an EFL context where teachers share the same L1 with students. Keywords: first language, English as a Foreign Language, sociocultural theory